2003
DOI: 10.1098/rspb.2002.2265
|View full text |Cite
|
Sign up to set email alerts
|

Variation in immune defence as a question of evolutionary ecology

Abstract: The evolutionary-ecology approach to studying immune defences has generated a number of hypotheses that help to explain the observed variance in responses. Here, selected topics are reviewed in an attempt to identify the common problems, connections and generalities of the approach. In particular, the cost of immune defence, response specificity, sexual selection, neighbourhood effects and questions of optimal defence portfolios are discussed. While these questions still warrant further investigation, future c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
578
5
3

Year Published

2004
2004
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 629 publications
(594 citation statements)
references
References 139 publications
8
578
5
3
Order By: Relevance
“…For instance, intestinal and other infections often result in decline in body mass, but without measuring digestive capacity, it would be impossible to distinguish whether the effect of infection on body mass was caused by depletion of bodily reserves, reduced food intake, or malabsorption. Such studies would thus importantly contribute to understanding the mechanisms of how exactly parasites and pathogens impinge on fitness, a goal often not attained in immunoecological research (e.g., Schmid‐Hempel, 2003). …”
Section: Discussionmentioning
confidence: 99%
“…For instance, intestinal and other infections often result in decline in body mass, but without measuring digestive capacity, it would be impossible to distinguish whether the effect of infection on body mass was caused by depletion of bodily reserves, reduced food intake, or malabsorption. Such studies would thus importantly contribute to understanding the mechanisms of how exactly parasites and pathogens impinge on fitness, a goal often not attained in immunoecological research (e.g., Schmid‐Hempel, 2003). …”
Section: Discussionmentioning
confidence: 99%
“…We limit our analysis to trade-offs between reproduction and immunity that are due to the evolutionary cost of maintaining a high immunity level, rather than the cost of mounting an immune response after infection (Schmid-Hempel, 2003). Such maintenance costs are apparent in the cellular defense response in insects.…”
Section: Model Descriptionmentioning
confidence: 99%
“…Recent models have shown that the evolutionary dynamics of host-parasite models may differ depending on whether hosts try to fight off parasites through lower transmission rates, higher recovery rates, or higher tolerance (Boots and Bowers, 1999;van Boven and Weissing, 2004). Models have also explored the cost of maintaining the baseline level of immunity, versus the cost that is incurred when genes are up-regulated in response to a parasite (Kraaijeveld et al, 2002;Lochmiller and Deerenberg, 2000;Schmid-Hempel, 2003). The costs of up-regulating defense machinery are only incurred by the infected individuals, whereas the standing costs for maintaining the immune system are incurred by both susceptible and infected individuals.…”
Section: Within-population Models Of Host-parasite Dynamicsmentioning
confidence: 99%
See 1 more Smart Citation
“…If the response to infection represents an adaptive shift in life‐history strategy, we would expect that infected animals would benefit appreciably more from inhabiting the preferred temperature than control animals; we would expect that the temperature preference would provide benefits one life‐history trait at a cost to other traits; and we would expect that the response ultimately results in increased offspring production for infected animals. This is especially of interest to ecological immunologists as all host defence traits are expected to be costly and trade‐off with other host life‐history traits (Sheldon & Verhulst 1996; Schmid‐Hempel 2003). …”
Section: Introductionmentioning
confidence: 99%